Effects of eyestalk ablation and limb autotomy on moulting, growth and survival rate of orange mud crab, Scylla olivacea juveniles for the production of soft-shell crabs - Mhd Ikhwanuddin; Hanafiah Fazhan; Wang, Youji; Chong, Alexander Shu-Chien; Abualreesh, Muyassar H.; Mohamad Jalilah; Ambok Bolong Abol-Munafi; Khor, Waiho (Penerbit Universiti Kebangsaan Malaysia, 2025)
Soft-shell crabs are highly sought after due to their ease of storage and can be eaten whole, including the outer carapace. The high demand for soft-shell crabs leads to the exploration of different production techniques and methods. This study explores the effect of limb autotomy, eyestalk ablation and their combinations on the duration and success rate till the next moulting, and the size increment and survival rate of male juveniles of Scylla olivacea after moult. Additionally, female juveniles were also subjected to limb autotomy to investigate the potential impact of sex on their response to the procedure. Full limb autotomy (T2), either alone or with eyestalk ablation (T4), induced the fastest moulting (average 33 d and 39 d, respectively), followed by eyestalk ablation (average 57 d) and control (average 82 d). Limb autotomy, either alone or with eyestalk ablation, resulted in 100% and 90% moulting success, respectively, whereas that of eyestalk ablation and control was 50% and 56.83%, respectively. Crabs subjected to both moult-inducing techniques had the lowest size and weight gain after moulting. Females moulted faster than males in natural conditions, but this was negligible when limb autotomy was introduced. Limb autotomy had no impact on the CW increment and survival rate of both sexes, but greatly reduced their BW increment. Thus, limb autotomy can be incorporated in the production of soft-shell crabs to reduce turnover time.